Solubility and Dissolution Rate Enhancement of Poorly Soluble Telmisartan using Hydrotropy Method (Asian Journal of Pharmaceutics (AJP), 2024)
Objectives: Drugs given by oral route will undergo dissolution followed by permeation then it reaches to blood.Low water solubility is the foremost issue that comes upon with the development of dosage forms for newlydiscovered drugs as well as old drugs. Telmisartan is a class II category drug under the biopharmaceuticalclassification system, which limits its bioavailability to about 40%. Hydrotropy method has several advantagescompared to other methods such as cost-effectiveness, ease of process, compatibility, scalable, and flexibilityto varieties of dosage forms. Henceforth, an attempt has been made to improve the solubility of telmisartanusing the hydrotropy method. Materials and Methods: Three different hydrotropic agents (urea, mannitol,and lactose) in different concentrations (10–50%) were used to find the solubility of the drug. The designof an expert statistical tool was utilized to optimize the best concentration of hydrotropic agent for havingmaximum solubility of the drug. Results: In a 40% urea blend, the solubility was obtained approximately25.87 times more than pure drug (0.003 mg/mL) which showed the potential of the hydrotropic agent. Thisobtained optimized batch was further characterized for drug release profile and other related parameters. Theoptimized concentration of urea showed 87.46 ± 0.17% of drug release in 8 h which is relatively higher thanthe plain drug release. Conclusion: Therefore, it can be concluded that the 40% concentration of urea as ahydrotropic agent showed to be a key factor for enhancement of solubility followed by dissolution of poorlysoluble telmisartan drug.